Finite element analysis of biomechanical investigation on diverse internal fixation techniques in oblique lumbar interbody fusion - Qi Yu; Zhuo Lin Zou; Hui Gen Lu; Xue Kang Pan; Xu Qi Hu; Zhong Hai Shen (BMC Musculoskeletal Disorders, 2024)
Abstract Background To establish a three-dimensional finite element model of the lumbar spine and investigate the impact of different fixation techniques on the biomechanical characteristics of oblique lumbar interbody fusion (OLIF). Methods The study aimed to establish and validate a comprehensive three-dimensional model of the lower lumbar spine (L3-S1) using the finite element method. L4-L5 was selected as the surgical segment, and four distinct OLIF surgical models were constructed: Stand-alone (SA), unilateral cortical bone trajectory screw (UCBT), bilateral cortical bone trajectory screw (BCBT), and bilateral pedicle screw (BPS). The models were underwent a pure moment of 10N·m to simulate lumbar extension, flexion, left bending, right bending, left and right rotation movements. Subsequently, the range of motion (ROM), cage stress, and fixation stress were calculated. Results In the L3-L5 segment, the BCBT group showed the most limited range of motion (ROM) under exercise load, indicating superior stability within this group. The ROM and cage stress values were found to be highest in the SA group. In contrast, the cage and internal fixation stress in the BPS group were observed to be lowest (9.91 ~ 53.83MPa, 44.93 ~ 84.85 MPa). With the exception of right bending and right rotation, the UCBT group demonstrated higher levels of internal fixation stress (102.20 ~ 164.62 MPa). Conclusions The study found that OLIF-assisted internal fixation improved segmental stability and reduced cage stress. The BPS group had advantages over the CBT group in preventing endplate damage and reducing the risk of cage subsidence. However, BCBT group has distinct merits in maintaining surgical segment stability, distributing stress load on the spinal motor unit, and reducing the likelihood of adjacent segment degeneration (ASD).